2004
DOI: 10.1103/physrevlett.92.062301
|View full text |Cite|
|
Sign up to set email alerts
|

Azimuthal Anisotropy at the Relativistic Heavy Ion Collider: The First and Fourth Harmonics

Abstract: We report the first observations of the first harmonic (directed flow, v(1)) and the fourth harmonic (v(4)), in the azimuthal distribution of particles with respect to the reaction plane in Au+Au collisions at the BNL Relativistic Heavy Ion Collider (RHIC). Both measurements were done taking advantage of the large elliptic flow (v(2)) generated at RHIC. From the correlation of v(2) with v(1) it is determined that v(2) is positive, or in-plane. The integrated v(4) is about a factor of 10 smaller than v(2). For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…In earlier analyses, v 4 was determined with respect to the event plane from elliptic flow [49,50] Figure 4 shows the results for v 5 , which are very similar to the results for v 4 . Here, the nonlinear term ε 2 ε 3 becomes important even for central collisions.…”
Section: Quadrangular Flowsupporting
confidence: 65%
“…In earlier analyses, v 4 was determined with respect to the event plane from elliptic flow [49,50] Figure 4 shows the results for v 5 , which are very similar to the results for v 4 . Here, the nonlinear term ε 2 ε 3 becomes important even for central collisions.…”
Section: Quadrangular Flowsupporting
confidence: 65%
“…In the three-particle correlation technique, the explicit determination of the event plane is not required; instead, the role of the event plane is played by the third particle that enters the correlator with double the azimuth [21,23,29]. Under the assumption that particle c is correlated with particles α and β only via common correlation to the reaction plane, we have…”
Section: Methodsmentioning
confidence: 99%
“…(4) to measurements of anisotropies in particle production with respect to the reaction plane is due to processes when particles α and β are products of a cluster (e.g., resonance, jet) decay and the cluster itself exhibits elliptic flow [21,23]. Detailed discussion of this and other effects which could mimic the effect of local strong P violation in experimental measurements is presented in Sec.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the models using hydrodynamic calculations [62] and jet energy loss ones [66] are observed to be in good agreement with the v 2 data at low and high p T , respectively. At RHIC [74,75] and LHC [7] it had been observed that the ratios of harmonics follow a power-law scaling, i.e. v Figure 6.…”
Section: Jhep07(2018)103mentioning
confidence: 99%